Optimalisasi Pemahaman Siswa SD pada Bahasa Indonesia melalui Pendekatan Culturally Responsive Teaching dengan Model Kooperatif Tipe JIGSAW: Penelitian - Wahyu Prihatiningsih; Ziana Walidah Tri Utami; Bela Kusuma Putri; Ika Candra Sayekti; Munawaroh Tri Handayani (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This research aimed to improve the understanding of fourth-grade elementary school students in Indonesian language subject, specifically concerning transitive and intransitive sentences, through the implementation of a Culturally Responsive Teaching (CRT) approach integrated with the JIGSAW cooperative learning model. This study employed a Classroom Action Research (CAR) method, conducted across two cycles. Each cycle comprised four stages: planning, implementation, observation, and reflection. This research encompasses planning that integrates CRT and JIGSAW with culture-based methods, media, and evaluation; implementing Indonesian language learning with cultural content and student grouping; observing student interactions and reactions; and reflecting on and analyzing data to measure the effectiveness of the approach in enhancing student understanding of transitive and intransitive sentences. The subjects of the research were 25 fourth-grade students at SDN Karangasem 1 Surakarta in the academic year 2024/2025. The data were analyzed quantitatively. The results demonstrated a significant increase in student understanding. In the first cycle, the percentage of students achieving mastery was only 44%. Following the implementation of actions in the second cycle, the mastery percentage significantly rose to 96%. These findings indicate that the CRT approach combined with the JIGSAW cooperative model is effective in optimizing the understanding of transitive and intransitive sentences among fourth-grade students at SDN Karangasem 1 Surakarta.